Starting Fire with Gunpowder revisited: Inuktitut New Media content creation in the Canadian Arctic - Pasch, Timothy (Études/Inuit/Studies, 2010)
In 1991, the Canadian documentary Starting Fire with Gunpowder was produced, focusing in part on the history of early media productions by the Inuit Broadcasting Corporation (IBC). It examined how the creation of Inuktitut media content could be an effective means of creative improvisation, linguistic and cultural preservation, and transmission of traditional knowledge. Almost 20 years later, the Internet serves as one of the primary communicative methods for young Inuit in the Canadian Arctic. However, it remains to be seen whether the quality of Inuktitut media online can compare with the example of linguistic and cultural preservation set by the visionaries of the early IBC. This article challenges prevailing critical approaches to the Inuit as linguistically and culturally vulnerable. It views Inuktitut New Media content as an embodiment of the word airaq (‘edible roots’), used here as a model of strength, resilience, and adaptability. It concludes that the creativity and prolificacy of the early IBC productions should set the standard for a new generation of Inuktitut content creators online.